Fabrication, characterization and adsorption properties of cucurbit[7]uril-functionalized polycaprolactone electrospun nanofibrous membranes - Chen, Changzhong; Liu, Fengbo; Zhang, Xiongzhi; Zhao, Zhiyong; Liu, Simin (Beilstein Journal of Organic Chemistry, 2019)
The fabrication of electrospun nanofibers comprising cucurbit[7]uril (CB[7]) and poly(ε-caprolactone) (PCL) is reported. Various techniques such as SEM, FTIR, XRD, DSC and TG were utilized to characterize the morphology, composition and properties of the nanofibers. Uniform bead-free electrospun nanofibers were obtained from PCL/CB[7] mixed solutions and the average fiber diameter of the nanofibers increases with the increase of CB[7] content. The nanofibers are composed of a physical mixture of PCL and CB[7], and CB[7] itself is present in the PCL fiber matrix in an uncomplexed state. The static adsorption behavior of the PCL/CB[7] nanofibers towards methylene blue (MB) was also preliminary investigated. The results indicate that the adsorption of MB onto the nanofibrous membranes fits the second-order kinetic model and Langmuir isotherm model.
Keywords: adsorption; cucurbit[7]uril; electrospinning; macrocycles; methylene blue; nanofiber